2017
DOI: 10.1038/ctg.2016.66
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of Methylated SEPT9 for Blood-based Colorectal Cancer Detection: A Systematic Review and Meta-Analysis

Abstract: Objectives:More convenient and effective blood-based methods are believed to increase colorectal cancer (CRC) detection adoption. The effectiveness of methylated SPET9 for CRC detection has been reviewed in the newly published recommendation statement by US Preventive Services Task Force (USPSTF), while detailed instructions were not provided, which may be a result of insufficient evidence. Therefore, more evidence is needed to assist practitioners to thoroughly understand the utilization of this special maker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
69
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(77 citation statements)
references
References 32 publications
6
69
0
2
Order By: Relevance
“…Stool‐based assays like the FIT are less invasive but have limited ability to detect premalignant colorectal adenomas. Recently, tumor‐derived cell‐free nucleic acids released in stool and blood have emerged as promising biomarkers in cancer, and tests for the detection of cell‐free nucleic acids such as the stool‐based DNA multimarker (ColoGuard®), or the blood‐based test for detection of methylated Septin 9 DNA have been developed . However, a major proportion of early stage tumors does not release detectable amounts of circulating tumor DNA, even when extremely sensitive techniques are used for their identification …”
Section: Discussionmentioning
confidence: 99%
“…Stool‐based assays like the FIT are less invasive but have limited ability to detect premalignant colorectal adenomas. Recently, tumor‐derived cell‐free nucleic acids released in stool and blood have emerged as promising biomarkers in cancer, and tests for the detection of cell‐free nucleic acids such as the stool‐based DNA multimarker (ColoGuard®), or the blood‐based test for detection of methylated Septin 9 DNA have been developed . However, a major proportion of early stage tumors does not release detectable amounts of circulating tumor DNA, even when extremely sensitive techniques are used for their identification …”
Section: Discussionmentioning
confidence: 99%
“…An article published by Imperiale et al in the NEJM in 201414 described an FDA-approved stool-DNA test (Cologuard, Exact Sciences, Madison, Wisconsin, USA) and reported sensitivity of 42% for advanced adenomas and 92% for cancer, with a specificity of 87%. Other work has been done employing Septin 9 (Epigenomics), another FDA-approved test based on detection of methylation markers in blood samples 15. DiaCarta Inc., a molecular diagnostic based in Richmond (California), has developed a highly sensitive multiplex real-time qPCR assay that combines a multiplex colorectal gene specific panel7 8 with proprietary xeno nucleic acid (XNA) wild-type clamping probe technology.…”
Section: Introductionmentioning
confidence: 99%
“…Test performance (Table 1) was evaluated in a number of case control studies in Europe and China [27,[31][32][33][34]. As outlined in these studies, test sensitivity was reported to range from 73-81% and test specificity was reported to range from 96-99%.…”
Section: Epi Procolon 20 and The Us Fda Pma Approved Epi Procolonmentioning
confidence: 99%
“…A development project was undertaken to reduce the research observations to practice requiring standardization of each protocol step. The test was developed and optimized through different versions as outlined (Table 1) and the performance characteristics have been summarized in a meta-analysis including 25 studies [27]. …”
Section: Development and Clinical Performancementioning
confidence: 99%